(untitled) (Research, Society and Development, 2021)
Primary dysmenorrhea (PD) is called menstrual cramps and the appearance of symptoms may be associated with the action of prostaglandins (PG) and leukotrienes (LT). Essential fatty acids (AGEs), mainly ômega 3, have anti-inflammatory properties that inhibit PG synthesis. Thus, this systematic review aims to discuss the use of AGE supplementation in the treatment of PD. Original clinical trial studies, published between 2000 and 2021, were searched in the Pubmed and Scielo databases. Eight articles were included and analyzed in this study. Based on the results, it is stated that AGEs, especially ômega 3, are relevant in the treatment of PD, identifying as a mechanism of action the inhibition of cyclooxygenase activity by ômega-3, which leads to lower production of PG and LT pro-inflammatory, increasing the formation of its derivatives, anti-inflammatory. Therefore, it is suggested that dietary supplementation from 300 mg of ômega-3, 8-2 days before and up to 3-2 days after menstruation, especially after 2 months, reduces pain in women with PD.